Analisis Penggunaan Media Pembelajaran Interaktif Educaplay dalam Meningkatkan Minat Belajar Siswa Sekolah Dasar - Nafia Wafiqni; Fitri Adelia (Jurnal keilmuan dan Kependidikan dasar, 2025)
This study aims to determine the extent of the influence of using the Educaplay educational platform on elementary school students’ learning interest. This research uses a quantitative approach with experimental methods and a one group pretest-posttest design. The sample consisted of 22 students. Data collection techniques include questionnaires and documentation. The results showed that the use of Educaplay had a positive effect on students' interest in learning. The average pretest score of 61.18 became 73.86 in the posttest, with a difference of 12.68 points. The paired sample t-test shows a significance value of 0.000, which is smaller than 0.05, so h0 is rejected and ha is accepted. That is, there is a significant influence between the use of Educaplay and the increase in learning interest. The average N-Gain value of 58.21 is classified in the "Moderate" improvement category, with 64% of students in that category. This shows that Educaplay is effective in increasing students' overall interest in learning. Thus, the use of Educaplay was shown to have a significant impact on increasing elementary school students' interest in learning.